Prinsip dan Prosedur Pengelolaan Lingkungan Belajar di RA An-Nur Babalan - Annisaa Nur Faudillah; Aulia Fitriani Munthe; Alya Sabrina Ramdhan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The purpose of this journal is because there are still many kindergartens/RAs that do not fully understand the management of learning environments. This paper aims to understand and describe the findings of observations conducted at RA An-Nur Babalan regarding the management system of learning environments. Based on the findings of the study, RA An-Nur Babalan has successfully implemented a learning environment system. The stages of this research are descriptive qualitative research, where researchers try to describe and explain the object of research according to existing knowledge. The methods used in this study are observation and interviews. The data that has been collected is then analyzed through several steps, namely data collection, data reduction, data analysis, and conclusions. The findings of this study indicate that RA An-Nur Babalan can create a learning environment that involves students (invites them into the classroom), encourages them to be independent, and has implemented the process of using the learning environment, as well as applying several principles of the learning environment. This study can be used to support the idea that the learning process, which includes teaching students about their social, emotional, and intellectual environments, has a general purpose of providing a means for them to engage in various activities.